Simultaneous ROMP and titania sol–gel reactions and nanodispersed functional organic–inorganic composite hybrid materials - van Hensbergen, J.; Liu, M.; Burford, R.; Lowe, Andrew (R S C Publishing, 2015)
This contribution addresses the important issue of chemical, kinetic and thermodynamic matching in the one-pot preparation of organic–inorganic hybrid materials based on simultaneous titania sol–gel chemistry and ring-opening metathesis polymerization (ROMP). Few systems are amenable to concurrent and in situ sol–gel/polymerization processes, but the rapid rate and functional group tolerance of Grubbs' catalyst mediated ROMP impart ideal kinetic and chemical compatibility with β-diketone moderated sol–gel condensation. Hybrids containing targeted loadings of up to 20 wt% TiO2 nanoparticles, evenly dispersed throughout the organic matrix, were prepared with commercially available norbornene as well as a range of functional exo-7-oxanorbornenes synthesized via thiol-Michael coupling chemistry. The thermodynamic compatibility of these systems was further improved via the use of a novel triethoxysilane functionalized monomer to introduce strong C–Si–O–Ti– bonds between the organic and inorganic phases. The resulting covalently bound hybrids were molecularly homogeneous, optically transparent, orange in colour and behaved as acid degradable thermosets. Significantly, they could incorporate up to 75 wt% of Ti-based species (without phase separation), as well as various hydrophobic and functional comonomers for additional versatility and the modification of physical properties. Raman analysis suggested the Ti existed in an amorphous state while TGA analysis implied the presence of Ti-hydrates.